Pengaruh Harga dan Kualitas Pelayanan terhadap Keputusan Penggunaan Jasa Layanan pada JNE Express Tanjung Priok Jakarta Utara - Hermawan, Eric; Marliani, Vitri (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
The phenomenon in this research is related to the increasingly fierce competition in the shipping service industry. Some of the problems that occur regarding complaints of 'delivered' status sent but the package has not been received, the package received is wrong or confused with other packages, employees are not friendly in providing services, and payment transactions cannot use e-payment. The purpose of this research was to determine the impact of price and service quality on the decision to use services at JNE Express Tanjung Priok, North Jakatta. This research uses quantitative method with a descriptive analysis approach. The population is consumers at JNE Express Tanjung Priok North Jakarta. The sample was taken using the Slovin formula calculation. Data analysis using multiple linear regression models, T test, F test, and R2 coefficient of determination test. The results showed that simultaneously the variables Price and Service Quality affect the Decision to Use Services. This is evidenced by the results of the F test which has a significance value of 0.000